An evaluation of the relationship between vitamin d status and quadriceps strength in patients with copd: a cross sectional study. Issue 2 (20th January 2011) - Fenn, J; Martineau, A; Yee, J Wai; Islam, K; Griffiths, C; Maffulli, N; Morrissey, D
Abstract : Background: Quadriceps muscle weakness is a well-defined characteristic of chronic obstructive pulmonary disease (COPD). Vitamin D deficiency has been shown to be highly prevalent in COPD but its association with quadriceps strength in this group is unknown. Objectives: To investigate the effects of Vitamin D status on quadriceps strength. To validate measurements of quadriceps strength by handheld dynamometer (HHD) against the gold standard isokinetic dynamometer (IKD) in a sub-population. Methods: 30 patients with COPD Gold Stage II and above were recruited. Quadriceps muscle strength was tested using the HHD in all subjects. Eight of the subjects were also tested using the IKD for validation purposes. Vitamin D status and a range of potentially confounding measures were assessed. A multivariate analysis was performed to determine which variables were associated with quadriceps strength. Results: A very strong and positive correlation (r=0.92, 95%, p<0.0001), existed between the HHD and IKD measurements. Serum 25-hydroxyvitaminD was not associated with quadriceps strength (r=0.17, p=0.20). The male gender (β 36.7, 95% CI 14.0 to 59.4, p=0.002) and pack year history (β −0.15 95% CI −0.2 to −0.05, p=0.003) were independently associated with quadriceps strength. Conclusions: The portable and inexpensive HHD is a valid method of testing quadriceps strength in patients with COPD. Serum 25-hydroxyvitaminD is not associated with quadriceps strength in patients with COPD, although male gender and a decrease in pack year history are significantly associated.